Sector Innovation Report Aftermarket Consumables: Part 1: Latest Developments (Just Auto - News & Sector Market Reports, 2025)
According to the terms of the agreement, Standard Motor Products has acquired all issued and outstanding shares of Nissens for approximately $390 million (360 million), net of cash and assumed debt, and subject to post-closing adjustments. According to the company, the updated website provides visitors with comprehensive product information, expert advice, and a wealth of resources, such as technical data sheets and safety data sheets, all designed to enhance the customer experience. Cardholders from select financial institutions, such as Banco de Oro, EastWest Bank, and Bank of the Philippine Islands, are eligible to take advantage of this benefit.